Increasing Business Activity By Improving Employee Incentive System In Industrial Enterprises (Eurasian Journal of History, Geography and Economics, 2023)
In order to ensure adaptability to market changes in the textile industry, the article examines the issue of improving the financial incentive system of employees, taking into account their potential opportunities, to increase the activity of work.